2023
DOI: 10.1007/s13143-023-00320-w
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of The Performance of CMIP6 Models for Dynamic Downscaling in The North Pacific and Northwest Pacific Oceans

Abstract: Selecting a reliable global climate model as the driving forcing in simulations with dynamic downscaling is critical for obtaining a reliable regional ocean climate. With respect to their accuracy in providing physical quantities and long-term trends, we quantify the performances of 17 models from the Coupled Model Inter-comparison Project Phase 6 (CMIP6) over the North Pacific (NP) and Northwest Pacific (NWP) oceans for 1979–2014. Based on normalized evaluation measures, each model’s performance for a physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Notably, IPSL-CM6A-LR, MIROC6, and ACCES-CM2 exhibit outstanding individual skill, reinforcing the utility of MMM. Furthermore, in a previous study [20], the authors ranked ACCES-CM2 as the best for the wind variable in the NWP based on a performance score using the normalized RMSD and Taylor skill score. Therefore, the findings of this study also provide information about the alternative best choices aside from ACCES-CM2 in terms of individual CMIP6 model usage, as the earlier study did not include considerations for IPSL-CM6A-LR and MIROC6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, IPSL-CM6A-LR, MIROC6, and ACCES-CM2 exhibit outstanding individual skill, reinforcing the utility of MMM. Furthermore, in a previous study [20], the authors ranked ACCES-CM2 as the best for the wind variable in the NWP based on a performance score using the normalized RMSD and Taylor skill score. Therefore, the findings of this study also provide information about the alternative best choices aside from ACCES-CM2 in terms of individual CMIP6 model usage, as the earlier study did not include considerations for IPSL-CM6A-LR and MIROC6.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the best tool to investigate future conditions of oceanic and atmospheric processes is the latest version of Coupled Model Intercomparison Project Phase 6 (CMIP6) [18] since it provides projections based on different Shared Socio-Economic Pathways (SSPs) and distinct radiative forcing scenarios. Previous studies have assessed the results of CMIP6 models in the NWP region, such as [19,20]. The authors mostly focused on the performance models, which suggested that CMIP6 models generally have sufficiently good skills to reproduce the annual trends and variability of atmospheric or oceanic variables such as surface winds and ocean temperatures.…”
Section: Introductionmentioning
confidence: 99%